Folklore use of wild fruits by the Oraon tribe of Sarguja district of Chhattisgarh, India - Panda, Amrita Kumari; Bisht, Satpal Singh; Lakra, Shashi; Kumar, Ashish; Kerketta, Aseem; Mishra, Rojita; Panda, Koustava Kumar; Bisht, Satpal Singh; Kerketta, Sushma (Ethnobotany Research and Applications, 2022)
Background: Forests and trees are the major resources sustainably utilized by the tribals for their livelihood. The tribals communities have lived in and known the forests in an intimate manner and have also gathered information about possible use and conservation of forests and trees. In present times, however, the indigenous knowledge base that the tribals have gathered and preserved yet far has been endangered due to sociocultural hybridization as a result of modernization and globalization. This situation, hence, calls for an urgent need to device strategies to conserve tribal knowledge through various means. In this-respects, the present study attempts to survey, document and preserve the knowledge regarding the wild edible fruits consumed by Oraon tribes of Surguja district of Chhattisgarh and the Current status of the tribe concerning the interest towards the wild fruit collection, consumption and conservation. Methods: The study was undertaken during December 2019-July 2020. The information was obtained through semi-structured schedule. The importance of wild edible fruits as ethnomedicine was expressed through Informant Consensus Factor (ICF), Use Value (UV) and Relative Frequency of Citation (RFC). Results: A total of 26 wild fruit species, considered by the Oraon tribe to have medical values and ability to impart health benefits have been reported in this study. The reported fruit species belongs to 16 different families. Moraceae was the dominant family amongst the reported fruit species, the highest informant consensus factor (ICF) value was 0.94 for Liver related problems followed by Inflammation (0.91), Pain and Skin related disease as (0.86).The most frequently used fruit species were Morus alba (0.86), followed by Syzygium cumini (0.84), Diospyros melanoxylon, Madhuca longifolia and Neolamarckia cadamba (0.82) each, Ficus religiosa and Ziziphus mauritiana (0.80) each based on Relative frequency of citation. Conclusions: Furthermore, the documentation of diverse therapeutic practices of wild fruit species by the Oraon and several other tribes shall support further pharmacological research to develop novel future generation drug molecules. Keywords: Dietary nutrition, Folklore uses, Indigenous technical knowledge, Wild edible fruits.